2000
DOI: 10.2466/pr0.2000.86.3.1050
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of the Japanese Version of the Temperament and Character Inventory

Abstract: The Temperament and Character Inventory was translated into Japanese, and, to confirm the psychometric properties of the inventory, three samples were recruited from a nonpatient population. In nonpatient population A (N = 555), the full version (240 items) of the inventory with dichotomous measuring, along with the General Health Questionnaire and the Social Desirability Scale, were distributed to the subjects. Factor analyses of the subscales showed that the factor structure of the inventory was consistent w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(79 citation statements)
references
References 10 publications
2
76
0
Order By: Relevance
“…There are studies on the internal consistencies and factor structures of the Japanese versions [19,21,22]. The internal consistency (Cronbach's alpha) in this study was .773 for NS, .788 for HA, .696 for RD, .592 for PS, .802 for SD, .802 for CO, and .796 for ST.…”
Section: Personalitymentioning
confidence: 81%
See 1 more Smart Citation
“…There are studies on the internal consistencies and factor structures of the Japanese versions [19,21,22]. The internal consistency (Cronbach's alpha) in this study was .773 for NS, .788 for HA, .696 for RD, .592 for PS, .802 for SD, .802 for CO, and .796 for ST.…”
Section: Personalitymentioning
confidence: 81%
“…The Japanese version [19] of the TCI [20] was used. There are studies on the internal consistencies and factor structures of the Japanese versions [19,21,22].…”
Section: Personalitymentioning
confidence: 99%
“…The assessments included general socio-demographics, detailed information about the MVA, vital signs and physical condition on admission, past medical and psychiatric history, psychiatric family history, sense of the threat of death during the MVA, unconsciousness just after the MVA, loss of memory regarding the MVA referring to Gil's study (25), retrograde amnesia, feelings of self-reproach, physical pain, prior traumatic events, involvement in previous MVAs, consumption of alcohol prior to the MVA, and daily performance status (PS) as defined by the Eastern Cooperative Oncology Group (26). Psychometric instruments included the Impact of Event Scale revised (IES-R) (27,28), the Hospital Anxiety and Depression Scale (HADS) (29,30), the Peritraumatic Dissociative Experience Questionnaire (PDEQ) (31), and the Temperament and Character Inventory (TCI) (32,33). All participants were given a gift voucher for their participation after assessment (1,000 JPY for the initial interview).…”
Section: Methodsmentioning
confidence: 99%
“…The character dimensions consist of Self-Directedness (SD, 0-44), which refers to an individual's ability to control, regulate and adapt behavior in accord with individual goals and values, Cooperativeness (CO, 0-42), which indicates the tendency towards social tolerance, empathy, helpfulness and compassion, and Self-Transcendence (ST, 0-33), which refers to identification with nature and the ability to accept ambiguity and uncertainty (Cloninger, et al, 1994). The TCI's psychometric properties have been established in several countries, for example, the USA, Sweden, Japan, France, The Netherlands, and Korea (Duijsens, Spinhoven, Goekoop, Spermon, & Eurelings-Bontekoe, 2000;Kijima, Tanaka, Suzuki, Higuchi, & Kitamura, 2000;Brändström, Sigvardsson, Nylander, & Richter, 2008). The use of the TCI in different contexts of psychological research has also increased in the past 15 years and many studies have indicated high construct validity across populations (Brändström, Richter, & Przybeck, 2001).…”
Section: Questionnairesmentioning
confidence: 99%